1999
DOI: 10.1007/s004380050971
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and environmental response-specific expression of 10 PP2C transcripts in Mesembryanthemum crystallinum

Abstract: Ten transcripts (Mpc1-10) homologous to protein phosphatases of the 2C family have been isolated from the halophyte Mesembryanthemum crystallinum (common ice plant). Transcripts range in size from 1.6 to 2.6 kb, and encode proteins whose catalytic domains are between 24% and 62% identical to that of the Arabidopsis PP2C, ABI1. Transcript expression is tissue speci®c. Two isoforms are present only in roots (Mpc1 and Mpc5), three in young leaves (Mpc6, 8 and 9), two in old leaves (Mpc6 and Mpc8), and two in post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Membranes were washed three times in 2 · SSC with 0.5% SDS at 38°C for 1 h (DNA probe) or at 55°C for 1 h (LNA probe), and then analyzed by the BAS 1500 imaging analyzer (Fuji Film). Total RNAs were isolated from about 0.1-0.5 g of Arabidopsis leaves or floral inflorescences by the aurintricarboxylic acid (ATA) method (Nagy et al 1988), and then Northern blot hybridization for mRNAs was performed as described previously (Miyazaki et al 1999). …”
Section: Small Rna and Mrna Analysesmentioning
confidence: 99%
“…Membranes were washed three times in 2 · SSC with 0.5% SDS at 38°C for 1 h (DNA probe) or at 55°C for 1 h (LNA probe), and then analyzed by the BAS 1500 imaging analyzer (Fuji Film). Total RNAs were isolated from about 0.1-0.5 g of Arabidopsis leaves or floral inflorescences by the aurintricarboxylic acid (ATA) method (Nagy et al 1988), and then Northern blot hybridization for mRNAs was performed as described previously (Miyazaki et al 1999). …”
Section: Small Rna and Mrna Analysesmentioning
confidence: 99%
“…In plants, it has been demonstrated that plant PP2Cs play a role as negative regulators of drought, salinity, and cold-stress signaling (27,35,(43)(44)(45). Despite accumulating evidence indicating that PP2C-related phosphatases are pivotal regulators in signaling cascades, little is known about the regulation of enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, kinase associated protein phosphatase (KAPP) is known to be an important element in flower meristem development (Stone et al, 1994;Williams et al, 1997;Stone et al, 1998) and an alfalfa PP2C, MP2C, has been found to act as a negative regulator of a stress activated MAPK (Meskiene et al, 1998). In addition, ten PP2C transcripts, Mpcl-MpclO, of ice plant showed tissue-and environmental response-specific expression patterns (Miyazaki et al, 1999). Besides these, it was reported *Corresponding author; fax +82-54-279-2199 e-mail genean@postech.ac.kr that Ptc2p/Ptc3p of budding yeast dephosphorylated the major cyclin dependent kinase, Cdc28p, and Ptc4 of fission yeast was involved in the regulation of vacuole fusion (Cheng et al, 1999;Gaits and Russel, 1999).…”
mentioning
confidence: 99%